2021
DOI: 10.3390/sexes2020015
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Quality of Sexual Life of Patients Receiving Home Palliative Care in Poland

Abstract: Background: Quality of life, physical, psychic, and social functioning assessments in patients suffering from chronic, progressive, and incurable diseases are one of the most significant aims of the palliative care home teams. Sexuality and intimacy can be one of the most important elements of a person’s life, even at the end of it. Unfortunately, there is very little interest in this topic among medical staff of palliative care units. The objective of the study: The aim of this study was to assess the health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Cancer and its treatment can severely affect sexual health of people with advanced cancer. [1][2][3][4][5] It is estimated that sexual problems and dysfunction after cancer treatment ranges from 40% and up to 100%. 6,7 Research has shown that the impact of cancer on sexual health and satisfaction is more severe in people with advanced disease compared to patients with early-stage cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer and its treatment can severely affect sexual health of people with advanced cancer. [1][2][3][4][5] It is estimated that sexual problems and dysfunction after cancer treatment ranges from 40% and up to 100%. 6,7 Research has shown that the impact of cancer on sexual health and satisfaction is more severe in people with advanced disease compared to patients with early-stage cancer.…”
Section: Introductionmentioning
confidence: 99%